(untitled) (Sustainability in Debate, 2017)
This paper presents an analysis of the process of land grabbing in land occupied by traditional populations, emphasizing the participation of social movements and local families in the resistance process construction, decisive for the creation of a Conservation Unit for Sustainable Use in the Terra do Meio region, State of Pará. Twenty-three semi-structured interviews were conducted with families in the area, with audio recording and posterior transcription. Traditional populations of this region have always lived under constant pressure and threats to their ways of life and land rights, whether by rubber tappers, farmers, land grabbers, landholders, loggers and speculators. The scenario of coercion and land expropriation triggered a process of struggles and demands, resulting in the creation of Xingu River Extractive Reserve, aiming to guarantee territory and the maintenance of local families’ livelihoods.